Microstructure and mechanical properties of 17-4 PH stainless steel and Al2O3 ceramic joints brazed with graphene reinforced Ag-Cu-Ti brazing alloy. (November 2020) - Yang, Z.W.; Yang, J.H.; Han, Y.J.; Wang, Y.; Wang, D.P.
Abstract: 17-4 PH stainless steel and Al2 O3 ceramic were successfully vacuum brazed using graphene reinforced Ag-Cu-Ti brazing alloy. In this paper, the effects of operating parameter such as brazing temperature, holding time and graphene amount on the microstructure and mechanical properties of the brazed joints were systematically studied. The experiment revealed that with the elevation of brazing temperature and holding time, the shear strength of 17-4 PH stainless steel and Al2 O3 ceramic joints brazed with Ag-Cu-Ti filler alloy increased first, getting the maximum 170 MPa at 880 °C for 10 min and then declined. When the joint brazed with 0.1 wt % graphene reinforced Ag-Cu-Ti composite filler, the maximum shear strength reached 212 MPa that was 25% higher than the joint with single Ag-Cu-Ti filler metal. Moreover, fracture path of the 17-4 PH stainless steel and Al2 O3 ceramic joint with 0.1 wt % graphene reinforced Ag-Cu-Ti was changed from the ceramic to the reaction layer that was closed to Al2 O3 substrate. The improvement of the joint shear strength was chiefly benefited from the formation of TiC particle that reinforced brazing seam and the refinement of joint microstructure. Highlights: Graphene reinforced Ag-Cu-Ti composite filler was used to braze 17-4 PH stainless steel and Al2 O3 ceramic. Effect of brazing parameter and graphene content on the joint microstructure was studied. The joint shear strength reached 212 MPa when the graphene content was 0.1 wt %. A conceptual microstructural evolution mechanism of the joint was proposed.